Design and realization of low intermodulation three-frequency coaxial cavity combiner - Ge Xuefei; Zhang Xupu; You Bin (Dianzi Jishu Yingyong, 2022)
A three-frequency coaxial cavity combiner with low passive intermodulation is designed. By designing the tap structure of the common cavity and tuning its relative cavity position and optimizing the height of the steps between the resonant cavities, the intermodulation distortion is reduced, thereby reducing the third-order intermodulation. On the basis of meeting the design specifications, a low-intermodulation triple-frequency combiner based on DCS1800, TD-SCDMA2100, and WLAN2600 was designed, processed and measured. The measurement results satisfy that the third-order intermodulation values of the three frequency bands are less than -172.50 dBc, -169.75 dBc, and -173.30 dBc, respectively, and verify the feasibility of the design.